Pengaruh Dosing Bleaching Earth Terhadap Persen Oil Losses pada Proses Refinery Crude Palm Oil-Technical Oil (CPO-TO) - Dwi Anissa Fithry; Israyandi Israyandi; Bima Wandika Putra; Sopia Khairani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The refining process of crude palm oil (CPO-TO) into Refined Bleached Deodorized Palm Oil-Technical Oil (RBDPO-TO) requires a bleaching step to remove pigments and impurities. The use of bleaching earth (BE) at this stage plays a crucial role in improving oil quality, but has the potential to cause oil losses, which can reduce product yield. This study aims to analyze the effect of bleaching earth dosage on oil content, total oil losses, and RBDPO-TO yield in the refinery process. The study was conducted quantitatively using operational data and laboratory analysis results at PT XYZ Dumai during the period of December 1–14, 2025. The bleaching earth dosage varied between 0.8–1.5% with a relatively constant feed flow rate. The results showed a positive correlation between increasing bleaching earth dosage and oil content and total oil losses, and a negative correlation with RBDPO-TO yield. A high BE dosage (1.4–1.5%) resulted in the highest oil losses of up to 0.89% and the lowest yield of around 84.23%, while a lower BE dosage (0.8–0.9%) reduced oil losses to 0.50% and increased RBDPO-TO yield to 89.39%.